PRODUKSI GAS HIDROGEN DITINJAU DARI PENGARUH DUPLEX STAINLESS STEEL TERHADAP VARIASI KONSENTRASI KATALIS DAN JENIS AIR YANG DILENGKAPI ARRESTOR - Bow, Yohandri; Sari, Ayu Permata; Harliyani, Ayu Dwi; Saputra, Bayu; Budiman, Ria (KINETIKA, 2020)
The potential for renewable energy is converting water into hydrogen gas through the electrolysis process. Electrolysis is the process of separating water molecules into hydrogen and oxygen gas by flowing an electric current. The electrolysis process is influenced by the type and concentration of catalyst, electrode, and the salinity of raw material. The electrolysis reactor prototype equipped with an arrestor to reduce risk of work accidents due to flashback fire. The results showed that in electrolysis process salinity value would be directly proportional to the gas produced from electrolysis the highest volume of hydrogen gas produced with a salinity of 8 ppt 100 ppm with a current of 35A. In the addition of a catalyst in the electrolysis process with current strength of 35 amperes the highest volume of hydrogen produced was 1.1744 liters at a concentration of 0.1M, for NaOH and with H2SO4 a gas with a volume of 1.2199 liters and a concentration of 0,1 M and the highest efficiency was obtained at a concentration of 0.1M of 40.1503% for NaOH and 41.7063% for H2SO4. In the arrestor test, it was found that filler material for stainless steel wool, copper powder, and aluminum oxide can prevent flashback fire.